Cannabinoid, melanocortin and opioid receptor expression on DRD1 and DRD2 subpopulations in rat striatum - Oude-Ophuis, Ralph J.; Boender, Arjen J.; van Rozen, Rea; Adan, Roger A. (Frontiers in Neuroanatomy, 2014)
The striatum harbors two neuronal populations that enable action selection. One population represents the striatonigral pathway, expresses the dopamine receptor D1 (DRD1) and promotes the execution of motor programs, while the other population represents the striatopallidal pathway, expresses the dopamine receptor D2 (DRD2) and suppresses voluntary activity. The two populations integrate distinct sensorimotor, cognitive and emotional information streams and their combined activity enables the selection of adaptive behaviors. Characterization of these populations is critical to the understanding of their role in action selection, because it aids the identification of the molecular mechanisms that separate them. To that end, we used fluorescent in-situ hybridization to quantify the percentage of striatal cells that (co)express dopaminergic receptors and receptors of the cannabinoid, melanocortin or opioid neurotransmitters systems. Our main findings are that the cannabinoid 1 receptor is equally expressed on both populations with a gradient from dorsal to ventral striatum, that the opioid receptors have a preference for expression with either the DRD1 or DRD2 and that the melanocortin 4 receptor (MC4R) is predominantly expressed in ventral parts of the striatum. In addition, we find that the level of MC4R expression determines its localization to either the DRD1 or the DRD2 population. Thereby, we provide insight into the sensitivity of the two dopaminoceptive populations to these neurotransmitters and progress the understanding of the mechanisms that enable action selection.